Regulation of commodity derivative markets: Critical assessment of reforms in the EU - Karin Küblböck; Cornelia Staritz (Austrian Foundation for Development Research (ÖFSE), 2014)
Commodity prices that are increasingly determined on global commodity derivative markets are important for economic and social development. The historically unprecedented commodity price boom - combined with high volatility - since the early-2000s has led to a debate about the functioning of commodity derivative markets. In the context of an international political consensus on the necessity to reduce excessive speculation, the EU has introduced several reforms. They include important measures on improving transparency, limiting market power and strengthening regulatory authorities but their effectiveness will strongly depend on the implementation rules that are currently discussed. More interventionist regulations that address the fundamental problems of these markets and limit the dominance of financial investors were only marginally addressed.
Keywords: 330